Changes in the metabolome, lipidomein, and gut microbiota in Behçet’s disease - Shang, Chen; Ji, Sujuan; Hao, Wenting; Wei, Xiangyu; Yu, Jiani; Liu, Jiayi; Zhang, Baoguo (Frontiers in Cell and Developmental Biology, 2025)
BackgroundsThere is growing evidence that autoimmune illnesses are associated with the metabolome and microbiota. Because Behçet’s disease (BD) is not often diagnosed as a systemic disorder, the aim of this research was to investigate changes in gut flora and metabolites in BD patients.MethodsWe used 16S rRNA gut microbiota gene sequencing and UPLC-QTOF-MS analysis to gather stool and serum samples from 12 age-matched healthy controls and 17 BD patients. The correlation between changes in gut microbiota and metabolites was then further analyzed.ResultsIn contrast to healthy controls, our investigation revealed significant changes in the makeup of gut flora in BD patients. In particular, we observed that in the BD group, there was a large drop in clostridia but a noticeable rise in γ-proteobacteria and betaproteobacteria. The serum metabolomics profiles of BD patients and healthy controls may be reliably differentiated using unsupervised principal component analysis (PCA). Several metabolites, including L-phenylalaine, tricarballylic acid, beta-leucine, ketoleucine, ascorbic acid, l-glutamic acid, l-malic acid, d-glucopyranuronic acid, and methyl acetoacetate, were found to have differential expression between BD patients and healthy controls. All of these metabolites were significantly lower in the BD group. Furthermore, we discovered strong associations between the detected metabolites such as tricarballylic acid, L-malic acid, D-glucopyranuronic acid with certain microbial families, such Prevotellaceae and Alcaligenaceae.ConclusionPatients with BD were found to have significant changes in the makeup of their gut flora and metabolites.